Orexin in Rostral Hotspot of Nucleus Accumbens Enhances Sucrose ‘Liking' and Intake but Scopolamine in Caudal Shell Shifts ‘Liking' Toward ‘Disgust' and ‘Fear' - Castro, Daniel C (Neuropsychopharmacology, 2016)
The nucleus accumbens (NAc) contains a hedonic hotspot in the rostral half of medial shell, where opioid agonist microinjections are known to enhance positive hedonic orofacial reactions to the taste of sucrose (‘liking' reactions). Within NAc shell, orexin/hypocretin also has been reported to stimulate food intake and is implicated in reward, whereas blockade of muscarinic acetylcholine receptors by scopolamine suppresses intake and may have anti-reward effects. Here, we show that NAc microinjection of orexin-A in medial shell amplifies the hedonic impact of sucrose taste, but only within the same anatomically rostral site, identical to the opioid hotspot. By comparison, at all sites throughout medial shell, orexin microinjections stimulated ‘wanting' to eat, as reflected by increases in intake of palatable sweet chocolates. At NAc shell sites outside the hotspot, orexin selectively enhanced ‘wanting' to eat without enhancing sweetness ‘liking' reactions. In contrast, microinjections of the antagonist scopolamine at all sites in NAc shell suppressed sucrose ‘liking' reactions as well as suppressing intake of palatable food. Conversely, scopolamine increased aversive ‘disgust' reactions elicited by bitter quinine at all NAc shell sites. Finally, scopolamine microinjections localized to the caudal half of medial shell additionally generated a fear-related anti-predator reaction of defensive treading and burying directed toward the corners of the transparent chamber. Together, these results confirm a rostral hotspot in NAc medial shell as a unique site for orexin induction of hedonic ‘liking' enhancement, similar to opioid enhancement. They also reveal distinct roles for orexin and acetylcholine signals in NAc shell for hedonic reactions and motivated behaviors.